Køn og dømmekraft: Billedkunstens blinde punkt - Christensen, Hans Dam (Kvinder, Køn & Forskning, 2006)
Gender and Judgement: The Blind Spot of the Visual Arts ‘Quality’ is the foremost criteria, when Danish art museums collect artworks. At least that is what curators claim when it comes to gender, and most female artists agree: gender issues are second to quality. However, in this article the concept of ‘quality’ is an obstacle for a critical thinking of gender. ‘Quality’ does not exist as an autonomous analytic category in the field of the visual arts. On the contrary, it is depending on the agents’ habitus as well as the cultural and social processes of valuing in the field. Therefore, this article argues, ‘gender’ should be considered before ‘quality’, just as ‘periods’, ‘geography’, ‘-isms’, ‘motives’ and so on are naturalized analytic categories in the museums’ everyday which without trouble go before any concern of ‘quality’. The article is not aiming at an equal number of male and female artists’  represented in the museums, which would just reproduce the traditional concept of quality, but of an increased professional awareness of gender issues in all practices and discourses of art.